2016
DOI: 10.1093/jrr/rrv102
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the dose from natural radionuclides and artificial radionuclides after the Fukushima nuclear accident

Abstract: Due to the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, the evacuees from Namie Town still cannot reside in the town, and some continue to live in temporary housing units. In this study, the radon activity concentrations were measured at temporary housing facilities, apartments and detached houses in Fukushima Prefecture in order to estimate the annual internal exposure dose of residents. A passive radon–thoron monitor (using a CR-39) and a pulse-type ionization chamber were used to evaluate the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The reference value of the radon concentration in the radon chamber was based on the measurement values obtained from the standard ionization chamber. The details of the radon calibration chamber and the calibration conditions of AlphaGUARD at NIRS-QST were previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reference value of the radon concentration in the radon chamber was based on the measurement values obtained from the standard ionization chamber. The details of the radon calibration chamber and the calibration conditions of AlphaGUARD at NIRS-QST were previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The external dose estimation method in this study was different from that used by IYOGI et al Thus, although it is dif cult to compare these external doses directly, the annual effective doses seemed to have generally good agreement. Additionally, the nationwide average of the annual effective dose by terrestrial gamma-rays 16) is 0.33 mSv, and the average value for all of Aomori Prefecture was 59% of the nationwide average value. 169 ± 5 9 ± 1 9 ± 1 a The numbers refer to the designations in Fig.…”
Section: )mentioning
confidence: 96%
“…15) Portable type NaI(Tl) scintillation survey meters which were calibrated by the same ionization survey meter were used for this nationwide survey, and almost all the measurements were made on the grounds of schools located in each prefecture. 14) According to the results by this nationwide survey, 15,16) the arithmetic mean of absorbed dose rate in air by terrestrial gamma-rays was reported as 50 nGy h -1 , and the annual effective dose was 0.33 mSv. Two nuclear power plants (NPPs) and Japan's rst commercial nuclear fuel cycling facilities are located in Aomori Prefecture (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Namie is located in the northern part of Fukushima Prefecture in Japan, and its population was around 21,000 when the Great East Japan earthquake struck. Namie is located about 4 km away from the power plant and the residents were evacuated considering the impact of the accident [2], (Fig 1). The exposure of the thyroid to I-131 was considered problematic at the initial stages of the accident based on the lessons learned from the Chernobyl nuclear power plant [3,4].…”
Section: Introductionmentioning
confidence: 99%